The production of SPusp45-MSP-119 gene construct and its recombinant protein in Lactococcus lactis to be used as a malaria vaccine (Faculty of Medicine Universitas Indonesia, 2017)
Background: Merozoite surface protein 1 (MSP-1) is a major protein used by the Plasmodium during red blood cells invasion in malaria. MSP-119, one of MSP-1 is highly conserved, and it is a potential malaria vaccine candidate because the monoclonal antibodies are capable blocking erythrocyte invasion in vitro. The aim of this study was to produce MSP-119 gene construct and the recombinant protein in Lactococcus lactis. Methods: Usp45-MSP-119, derived from codon optimization and the synthetic gene, was inserted into the pMAT cloning vector. A vector expressing MSP-119 included usp45 has been constructed by the manipulation of recombinant DNA using restriction enzymes. The MSP-119 protein was expressed to 45% ammonium sulfate precipitation and purified using Sephadex-G50 gel filtration chromatography. The expressed protein was characterized by SDS-PAGE and dot blot. Results: usp45-MSP-119 gene was amplified using specific primers and inserted into the multiple cloning sites in the expression vector pNZ8148 with size 3,538 bp as a recombinant vector. The protein of MSP-119 was successfully expressed in L. lactis with molecular weight of 10.45 kDa. The dot blot was tested in 3 different comparisons between the host cells, non-induced cells, and induced cells with 10 ng/ml nisin. The results showed that 10 ng/ml nisin gave a positive reaction as detected by dot blot assay. Conclusion: This study confirmed that the usp45-MSP-119 gene was successfully inserted into the multiple cloning sites of the pNZ8148 expression vector and the MSP-119 protein expressed in the NICE system of the L. lactis host cell.